Determinant of Tax Avoidance: Empirical Study on Indonesia Stock Exchange - Amah, Nik; Puspitasari, Nadila Ayu; Syaifia, Anisa Rahmadita (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2022)
This study aims to examine the determinant of tax avoidance. The independent variables used in this study are financial distress, profitability, and audit quality. The dependent variable used in this study is tax avoidance. While the moderating variable in this study is firm size. The companies studied are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sampling technique is purposive sampling. The number of research samples used were 124 data. Data analysis used multiple linear regression, and Moderated Regression Analysis (MRA). The results of this study show that financial distress has no effect on tax avoidance. Profitability and audit quality affect tax avoidance. Firm size is not proven as an independent or moderating variable. The type of moderation in this study is homologizer moderator. Suggestions for companies to take every tax decision by taking into account the applicable tax laws and regulations. So that every tax planning decision made by the company does not harm the state.